Concept and mechanism for managing the digital transformation of Arctic target subspaces and spheres of vital activity. Issue 1 (September 2020) - Didenko, N I
Abstract: The present article considers a concept and mechanism for managing the digital transformation of Arctic target subspaces and spheres of vital activity. The necessary and sufficient conditions for choosing the concept and mechanism for managing the digital transformation of the development of the Arctic target subspaces and spheres of life are considered. The necessary conditions for the innovative and technological development of the Arctic territory, as well as the choice of concept and management mechanism, stem from the requirements of a set of measures that sustain human activity under the extreme conditions of the Arctic. Sufficient conditions for innovative technological development are determined by technological capabilities combined with a sufficient volume of investment in the global economy. The conceptual provisions of digital transformation are based on two main areas: (a) Industry 4.0 strategies adopted in various countries; (b) the main technological trends in the field of digital transformation of industry in the global economy. A schematic infrastructure for digital transformation of the technology-product life cycle of target subspaces and spheres of vital activity is presented along with a mechanism for managing the digital developmental transformation of Arctic target subspaces and spheres of life.